PERAN KOMUNIKASI KEPEMIMPINAN DALAM MENJAGA LOYALITAS KARYAWAN PADA TITILES DENPASAR - Murgawantari, Gusti Ayu Putu Yayang; Purnawan, Ni Luh Ramaswati; Alit Suryawati, I Gusti Agung (E-Jurnal Medium; Vol 1 No 1 (2017), 2017)
ABSTRAK The title of this research is “the role of leadership communication in maintaining the loyalty of the employees of Titiles in Denpasar, Bali. The aim of this research is to describe the role of leadership communication that has been done by the leader of Titiles, which has increased the loyalty of employees. This research applies descriptive qualitative method. The technique to gather the data in this research is depth interviews, observations and documentary studies. The technique to gather the 4 informants is purposive sampling. Great leadership communication skills that have been applied in Titiles also impacted the encouragement of employee’s loyalty. Through the applications of Barrett’s leadership communication (strategic objective, process, messages and communication staff) and Maslow hierarchy of needs theory principles (physiologies, secured, social, reward and self-conception) have also affected the loyalty of the employees. Keywords : Communication, Employee, Leadership, Loyalty, Titiles .